Virtual Expo Menggunakan Panggung sebagai Solusi Pameran Online di Masa Pandemi COVID-19 - Hery Budiyanto; Pindo Tutuko; Erna Winansih; Aries Boedi Setiawan; Muhammad Iqbal (University of Merdeka Malang, 2020)
Marketing of Micro, Medium and Small Enterprise (MSME) products through exhibitions is an effective means of selling MSME products. However, the COVID-19 outbreak that broke out in early 2020 has a significant impact on the lives of people around the world. Several online marketing alternatives can be done, including: e-Commerce, e-Marketplace, and Virtual Exhibition. Virtual exhibitions can be a solution amid the ban on crowding during large-scale social restrictions. Virtual exhibitions are events that can be watched on computers and cell phones using the internet directly (live streaming) or via Youtube channels from anywhere and anytime. The virtual exhibition and knitting craft workshop entitled